Identifying smart strategies for economic diversification and inclusive growth in developing economies: The case of Paraguay - Dominik Hartmann; Mayra Bezerra; Flávio L. Pinheiro (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
A country's productive structure determines its future path of economic diversification, economic growth, and income inequality. In this article, we identify Paraguay's structural constraints and opportunities for economic diversification and inclusive growth. For this purpose, we advance methods from research on economic complexity and the product space to estimate how feasible and desirable are different types of new products and economic diversification strategies for Paraguay. To estimate the feasibility of different diversification opportunities, we measure the revealed comparative advantages and relatedness of 763 SITC products to Paraguay's current product structure. To estimate the desirability of each product, we measure the expected level of income, economic complexity, technology and income inequality associated with these products. Our results indicate that despite Paraguay's strong dependence on primary goods and resource-based manufactures, it has significant opportunities to diversify into more complex, high-income, and inclusive products. These opportunities include manufacturing products related to agricultural activities (such as machines for harvesting or food-processing) as well as chemical products (such as medicaments and vaccines). We present a scoreboard of feasible and desirable product options that helps to discuss different diversification strategies. Paraguay could for instance (1) only focus on the relatedness criteria; (2) further develop the products with intermediate capabilities; (3) promote diversification into related, higher income products; or (4) push towards complex and inclusive industries. Our results imply that only focusing on feasibility may lead developing countries like Paraguay further into an economic development trap, consisting in the focus on simple products and the large distance to high complexity and low inequality products. Instead promoting products that combine minimum standards regarding both feasibility and desirability criteria might be the best strategy for smart diversification and inclusive growth.
urn:nbn:de:bsz:100-opus-16088
Keywords: 330; smart diversification; inclusive growth; product space; Paraguay